Dyeing Properties of Bamboo/Cotton Blended Yarns By Single-Bath Combined Process - (:unkn) unknown (ASIAN JOURNAL OF CHEMISTRY, 2012)
Nowadays the bioprocesses of cellulosic materials using various enzymes have almost become a common application, since they have many advantages over the conventional processes. These treatments undergo in mild and environmentally friendly conditions, compared to the conventionally carried out processes. Pectinase is used for scouring and catalase for removing the residual H2O2 in the bleach baths and on the fabric before the dyeing stage. In this work, C.I. Reactive Red 21 and C.I.. Reactive Blue 19 were used to dye untreated bamboo/cotton blended yarns by a single-bath combined process, in which various enzymes, namely, pectinase and catalase were employed. This process is completed almost in half of the conventional dyeing time and all of the stages, namely, scouring, bleaching and dyeing, were carried out in a single bath without replenishing of the process water until the end of the dyeing. In the single bath combined process, the untreated yarn was first scoured by pectinase and the yarn was then bleached by H2O2 in the same bath and after the hydrogen peroxide bleaching, the catalase enzyme was added to the bath to remove H2O2 residues before reactive dyeing. Without carrying out any intermediate washings/rinsing between these processes, the reactive dyeing was carried out by a conventional way in the same bath and finally the yarn was taken from the bath and washed to remove the unfixed dyes. The colour yield, dyeing fastnesses, dyeing repeatability and tensile strengths of the dyed materials were compared with those of the dyeing which were carried out conventionally in separate baths. The single bath combined process has many benefits in terms of water savings, reducing process times and energy consumptions, compared to the conventional preparatory and dyeing processes of bamboo/cotton-blended yarns.
Keywords: Enzymes; Combined-dyeing; Cellulosic and its blends dyeing; Bamboo; COTTON